Influência dos genes KIR e HLA de classe I na patogênese do HIV-1/aids em pacientes da região noroeste do Estado do Paraná, Brasil - Armi, Fernanda Formaggi Lara (2016)
The aim of this study was to investigate the NK cell count and the association of KIR and HLA class I genes with HIV infection and progression to AIDS. 99 blood samples from individuals were collected for the control group and 99 for the HIV group. The quantitation of NK cells was performed by flow cytometric methodology and classifying the KIR and HLA genes by PCR-SSOR. Statistical analysis was performed by Chi-square test with Yates correction or Fisher's exact test for categorical variables and the Mann-Whitney test for continuous variables. The NK cell count was lower in the HIV group compared to the control group and aids group in relation to without aids. The HLA-A*68:02 allele and the HLAA* 68_C*07 haplotype were more frequent in HIV group compared to the control group. The A*01:01 allele and some haplotypes formed by this allele were more frequent in the aids group in relation to without aids. The frequency of KIRD3L1-Bw4 / Bw4 combination was higher in the HIV group compared to the control. This study showed that NK cell count was lower in the group of HIV patients in the control group and AIDS in relation to without aids. In relation to genetic polymorphism, there was susceptibility to HIV-1 infection in the HLA-A*68:02 and HLA-A*68_C*07 presence. The A*01:01 allele was associated with progression to aids, as well as some haplotypes formed by this allele. The B*35, B*51, B*44 and B*08 allelic groups proved to be important in disease progression associated only when forming haplotypes. Regarding KIR genes, there was association of the KIR3DL1 gene with its HLA-Bw4 ligand in homozygous with HIV-1.